Prosedur Penerbitan Surat Ukur Kapal Baru Luncur Barge Patria 3222 pada KSOP oleh PT Menara Shipping Agency Batam - Tedi Kurniawan; Dirhamsyah Dirhamsyah; Yuna Sutria (Master Manajemen, 2024)
The purpose of writing this paper is to identify the Procedure for Issuing Measuring Letters for Newly Launched Barge Patria 3222 Ships at KSOP by PT Menara Shipping Agency Batam and to identify what are the obstacles or obstacles as well as solutions in issuing measuring letters for newly launched ships. This paper was written using field research methods, namely observation and interviews and library research methods. The results of this research state that the applicable procedures for issuing measurement letters for newly launched ships by KSOP Batam are in accordance with the regulations issued by the Minister of Transportation. The initial procedure that must be carried out by Barge Patria 3222 is to submit a request for measurements from Barge Patria 3222 to PT Menara Shipping Agency Batam. Then Barge Patria 3222 registered online on the KSOP website specifically for Batam (www.ksopkhususbatam.id) . The documents that have been submitted will be checked again by the Head of Ship Seaworthiness for approval. After approval, several surveyors are sent to carry out physical measurements of the ship and then the results are compiled into a report. If the report has been received, KSOP will verify and validate the report results. For issuance, the owner will be asked to wait some time to receive the newly released measurement letter.